Dissecting the molecular mechanisms underlying the antidepressant activities of herbal medicines through the comprehensive review of the recent literatures - Sun, Yilu; Zhao, Jia; Rong, Jianhui (Frontiers in Psychiatry, 2022)
Depression is clinically defined as a mood disorder with persistent feeling of sadness, despair, fatigue, and loss of interest. The pathophysiology of depression is tightly regulated by the biosynthesis, transport and signaling of neurotransmitters (e.g., serotonin, norepinephrine, dopamine, or γ-aminobutyric acid (GABA)) in the central nervous system. The existing antidepressant drugs mainly target the dysfunctions of various neurotransmitters, while the efficacy of antidepressant therapeutics is undermined by different adverse side-effects. The present review aimed to dissect the molecular mechanisms underlying the antidepressant activities of herbal medicines towards the development of effective and safe antidepressant drugs. Our strategy involved comprehensive review and network pharmacology analysis for the active compounds and associated target proteins. As results, 45 different antidepressant herbal medicines were identified from various in vivo and in vitro studies. The antidepressant mechanisms might involve multiple signaling pathways that regulate neurotransmitters, neurogenesis, anti-inflammation, antioxidation, endocrine, and microbiota. Importantly, herbal medicines could modulate broader spectrum of the cellular pathways and processes to attenuate depression and avoid the side-effects of synthetic antidepressant drugs. The present review not only recognized the antidepressant potential of herbal medicines but also provided molecular insights for the development of novel antidepressant drugs.